The Impact of Digital Marketing Strategies, Service Quality, and Social Media Engagement on Consumer Purchasing Decisions within E-commerce Platforms - Evan Ezar Ewardo; Diah Anggeraini Hasri (Universitas Muhammadiyah Enrekang, 2025)
The purpose of this study was to determine and examine the influence of Digital Marketing Strategy, Service Quality, and Social Media Use on Consumer Purchasing Decisions on e-commerce platforms in Sumbawa, NTB. The population in this study were all individuals in Sumbawa Regency who have or are using e-commerce platforms for purchasing transactions. The sampling method used convenience sampling with a total of 100 respondents. The research method used was a quantitative approach with an explanatory research design, and data analysis using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through SmartPLS 3.2.9 software. The results of the hypothesis test showed that Digital Marketing Strategy (X1) had a positive and significant influence on Consumer Purchasing Decisions (Y), as evidenced by a p-value of 0.011 (less than 0.05). Service Quality (X2) was also shown to have a positive and significant influence on Consumer Purchasing Decisions (Y) with a p-value of 0.043 (less than 0.05). Finally, Social Media Usage (X3) was found to have a positive and significant influence on Consumer Purchasing Decisions (Y) with a p-value of 0.042 (less than 0.05). The results of the f-square test further confirmed that the three independent variables had a significant influence, with Social Media Usage (0.437) showing a very strong impact compared to Digital Marketing Strategy (0.359) and Service Quality (0.342). This study concludes that optimizing digital marketing strategies, improving service quality, and utilizing social media effectively are key factors in driving consumer purchasing decisions in e-commerce, especially in Sumbawa